Endovascular treatment of a supraclinoid internal carotid artery fenestration aneurysm: A case report and literature review - Zibo Zhou; Jinlu Yu (Heliyon, 2023)
Supraclinoid internal carotid artery (ICA) fenestration aneurysm is rare. Except for open surgery, endovascular treatment (EVT) is considered an alternative for such an aneurysm. However, experience with this procedure is lacking. Therefore, we reported such a case. A 61-year-old woman suffered subarachnoid hemorrhage. Digital subtracted angiography (DSA) showed bilateral middle cerebral artery (MCA) aneurysms and a saccular aneurysm associated with fenestration of the supraclinoid ICA. Two MCA aneurysms were treated with single coiling, and the supraclinoid ICA fenestration aneurysm was coiled under stent assistance. The postoperative recovery was uneventful. At this time, a literature review was performed on the role of EVT in supraclinoid ICA fenestration aneurysms. A total of 13 supraclinoid ICA fenestration aneurysms treated by EVT in 11 cases, including our case, were obtained. After EVT, good outcomes were obtained in all cases. To our knowledge, this is the first study to review the role of EVT for supraclinoid ICA fenestration aneurysms. Our case report and literature review indicated that EVT for such aneurysms may be feasible and act as a therapeutic alternative.